Analysis of Extraordinary Optical Transmission With Periodic Metallic Gratings Using ADE-LOD-FDTD Method - Tu-Lu Liang; Wei Shao; Sheng-Bing Shi; Haiyan Ou (IEEE Photonics Journal, 2016)
In this paper, a frequency-dependent locally one-dimensional finite-difference time-domain (LOD-FDTD) method is developed for the extraordinary optical transmission (EOT) analysis of periodic metallic gratings. The dispersion of the metal, caused by the evanescent waves propagating along the interface between the metal and the dielectric materials in the visible and near infrared regions, is expressed by the Drude model and solved with a generalized auxiliary differential equation (ADE) technique. With efficient preprocessing for the lower–upper (LU) decomposition in ADE-LOD-FDTD, the periodic boundary condition (PBC) is applied to the 2-D metallic grating structure. Two numerical examples with different subwavelength slits are calculated, and the mechanism of the EOT phenomenon is investigated. Compared with the standard ADE-FDTD method, the results from the proposed method show its good efficiency for the nanostructures.